СТРАТЕГІЧНЕ УПРАВЛІННЯ В УМОВАХ РИЗИКУ ТА НЕВИЗНАЧЕНОСТІ - Verbovskyi, Igor (Zhytomyr Ivan Franko State University, 2024)
The relevance of the scientific study of the essence and importance of strategic management in conditions of risk and uncertainty is due to the challenges of the times, characterized by crisis conditions in many areas of economic activity and life support, as well as the growth of competitive conditions for various segments of the business environment. The research methodology is based on the principles of science and systematicity. To analyze the essential features of strategic management and to study the significance of applying modern innovative approaches to analyze and monitor certain changes under conditions of risk and uncertainty, the author uses the methods of comparative analysis, analytical and synthetic, statistical, abstract and logical. Although, at first glance, the results of scientific research on a wide range of scientific issues related to strategic management have been published, the requirements of the times require further research not only in general, but also taking into account the specifics of various sectors of the economy, in particular in conditions of uncertainty, the crisis in the Ukrainian economy, etc. To reveal the essence and significance of strategic management in the context of risk and uncertainty in the business environment, the author presents in more detail the characteristics of the main criteria and levers of influence on the formation of the basic foundations of strategic management. The advantages and disadvantages characterizing the peculiarities of the activities of enterprises in various sectors of the economy are determined, taking into account modern levers of influence. The author proves the special importance of taking into account external and internal factors that have an impact or may, under certain circumstances, affect the activities of enterprises both in conditions of stable development and taking into account conditions of risk and uncertainty. The study provides grounds to summarize the existing experience of enterprises of various forms and types of business and to assert the importance of planning their activities not only for short and medium-term periods in a competitive environment, but also to think strategically, anticipating and overcoming crisis situations and conditions of uncertainty, directing their efforts towards sustainable (balanced) development.